Durability of hepatitis B surface antigen seroclearance in untreated and nucleos(t)ide analogue-treated patients - Yip, Terry Cheuk-Fung; Wong, Grace Lai-Hung; Wong, Vincent Wai-Sun; Tse, Yee-Kit; Lui, Grace Chung-Yan; Lam, Kelvin Long-Yan; Chan, Henry Lik-Yuen (Journal of hepatology, 2018)
[Display omitted] •Seroclearance of HBsAg is regarded as functional cure of chronic hepatitis B.•Nucleos(t)ide analogues (NA)-induced HBsAg loss is as durable as spontaneous one.•Presence of anti-HBs is not essential for maintaining HBsAg seroclearance after NA.•No patients who had consolidation therapy >12months developed HBsAg seroreversion. It is uncertain if nucleos(t)ide analogue (NA)-induced hepatitis B surface antigen (HBsAg) seroclearance is durable. We investigated the impact of hepatitis B surface antibody (anti-HBs) and duration of consolidation antiviral therapy on the durability of HBsAg seroclearance. A territory-wide cohort study was conducted using data from the Hospital Authority, Hong Kong. We identified all subjects with positive HBsAg between January 1, 2000 and August 31, 2016. NA use, liver biochemistries, serial HBsAg and anti-HBs results were retrieved. The primary endpoint was confirmed HBsAg seroclearance, defined least two negative HBsAg test results, with the last HBsAg test being negative in patients with chronic hepatitis B (CHB). A total of 4,080 CHB patients were included for analysis. In patients with spontaneous HBsAg seroclearance (n=3,563), 1,771 patients (49.7%) had confirmed HBsAg seroclearance and 75 patients (2.1%) had HBsAg seroreversion. In patients with NA-induced HBsAg seroclearance (n=475), 320 patients (67.4%) had confirmed HBsAg seroclearance and 14 patients (2.9%) had HBsAg seroreversion. The five-year cumulative probability of confirmed HBsAg seroclearance was comparable in patients with spontaneous and NA-induced HBsAg seroclearance (88.1% vs. 92.2%; Log-rank test, p=0.964); it was also similar in patients with or without anti-HBs in NA-treated patients (95.4% vs. 95.5%, Log-rank test, p=0.602). HBsAg seroreversion was only observed in 3 (2.0%) patients who had received consolidation therapy for 6–12months and none of those who had received it for ≥12months. NA-induced HBsAg seroclearance is as durable as spontaneous HBsAg seroclearance. NA-treated patients may not need to have positive anti-HBs before stopping treatment. Longer consolidation NA treatment may result in more durable HBsAg seroclearance. We investigated 4,080 patients with hepatitis B surface antigen (HBsAg) seroclearance. HBsAg seroreversion occurred in 2.1% of patients with spontaneous and 2.9% of those with nucleos(t)ide analogues-induced HBsAg seroclearance.